PERTANGGUNGJAWABAN ADVOKAT DALAM PELANGGARAN KODE ETIK PROFESI PADA KLIEN - sari, nike kumala; Puruhita, Prasetyawati; Inka, Shalom; Rafael, Aldi; Liauw, Jonathan; Sally, Jeane Neltje (Peneliti.net, 2023)
A person who works in the legal profession is known as an advocate. An advocate is someone who offers legal help both inside and outside of court based on the principles of the advocate's code of ethics and includes standards based on the provisions of the advocate law. A person who works in a profession must adhere to certain standards of conduct in order to fulfill their duties. The application of a professional code of ethics is helpful in ensuring that advocates act with high integrity and professionalism and do not stray from the principles of the code in order to further their own interests. It also helps to prevent advocates from providing proper legal services. community so that supporters can be trusted by the populace. The study methodology employed is normative legal research, which is founded on written works, legal doctrine, legislation, and rules. The goal of this research is to identify the legal repercussions for advocates who transgress the code of ethics while performing their professional responsibilities. In accordance with Article 6 of Law of the Republic of Indonesia Number 18 of 2003 Concerning Advocates, which has regulated the presence of an ethics code, In order to protect the role of advocates in carrying out their responsibilities and uphold professional standards, profession is crucial.